Prevalence of head Lice (Pediculus humanus capitis) among primary schools pupils in Nassirya city (Baghdad Science Journal, 2008)
This study showed the spreading of head lice in pupils of primary schools of Al-Nassirya city.The results showed that the percentage of males infected with lice was (5.4 %) and (9 %) for females. Also was obtained difference at age groups which we found maximum percentage of infection at age between (8 – 11) year. The highest infection for the hair tall at medium tall for both sex which the ratio (35.2 %) while for both sex with ratio (25 %) for girls. While the highest percentage for straight hair was (14.8 %) for girls